Generalized linear methods and gap tauberian remainder theorems - Meronen, Olga; Tammeraid, Ivar (Mathematical Modelling and Analysis, 2008)
Some gap Tauberian remainder theorems are proved for generalized linear methods A = (Ank) , where Ank are bounded linear operators from Banach space X into X. In these theorems the investigated sequences have infinitely many constant pieces. First Published Online: 14 Oct 2010